Morphological and histochemical features of the cloaca of Turkey hen Meleagris Gallopavo - Mohammed, Lamees Ezaldeen (The Iraqi Journal of Veterinary Medicine, 2017)
The study includes six adult healthy hen turkey. The cloaca has three compartments separated by two circular folds and next to rectum is the coprodeum which the largest and measured (2.5±0.2cm) in length and (2.1±0.1cm) in diameter. The middle and smallest is the urodeum that measured about (1.01±0.2cm) in length and (1.2±1cm.) in diameter, that receives the ureter and left oviduct. Posteriorly, the proctodeum that measured about (1.4±0.1cm) in length and (1.6±1cm.) in diameter. The coprodeum mucosa has short and flat villi. The urodeum mucosa has tall branching pyramidal mucosal villi. The mucosa of proctodeum has lost the villi pattern. The three compartments were lined with mucous secreting columnar cells, most of these epithelial cells were positive for Alcian blue (2.5pH) stain and few were positive for PAS stain. The epithelial tubular glands showed positive reaction for Alcian blue satin only. The lamina propria of these compartments was cellular loose connective tissue displayed numerous of lymphatic nodules. The muscular mucosa is lost in proctodeum only. Tunica muscular is composed of two layers of smooth muscles fibers in coprodeum and urodeum and turned into skeletal type in proctodeum. The mean height of mucosal villi has significantly increased in urodeum.